Synthesis of framework Ti-substituted, 3-D hexagonal, mesoporous Ti-SBA-12 for selective catalytic oxidation - Kumar, Anuj; Srinivas, Darbha; Ratnasamy, Paul (Chemical Communications, 2009)
Framework Ti-substituted, 3-D hexagonal mesoporous, Ti-SBA-12, obtained for the first time by direct hydrothermal synthesis, oxidises bulky molecules such as cyclohexene and cyclooctene to the epoxides with >96% selectivity at high conversion levels (>60%).

Aminolysis of epoxides catalyzed by three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16 - Kumar, Anuj; Srinivas, Darbha (Journal of Catalysis, 2012)
The application of three-dimensional, mesoporous titanosilicates (Ti-SBA-12 and Ti-SBA-16) as reusable, solid catalysts for the synthesis of a range of beta-amino alcohols in high yields and selectivity through ring-opening of epoxides with amines at ambient and solvent-free conditions is reported, for the first time. These mesoporous titanosilicates (Si/Ti = 20-80) were prepared by a direct hydrothermal synthesis route adjusting the concentration of HCl (0.05-2 M) used in the synthesis. Ti ions in these catalysts were mostly substituted for Si in the framework. Water adsorption and Si-29 magic-angle spin nuclear magnetic resonance spectroscopy revealed that Ti-SBA-16 is more hydrophobic than Ti-SBA-12. Mesoporosity, three-dimensional architecture, surface hydrophobicity and easy access of Lewis acidic, framework-substituted Ti sites are the factors responsible for the superior activity of Ti-SBA-16 compared to Ti-SBA-12 and the hitherto known solid catalysts for this reaction. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Aminolysis of epoxides; beta-Amino alcohol; Mesoporous titanosilicates; Molecular sieves; Ring opening of epoxides with amines; Ti-SBA-12; Ti-SBA-16

Selective oxidation of cyclic olefins over framework Ti-substituted, three-dimensional, mesoporous Ti-SBA-12 and Ti-SBA-16 molecular sieves - Kumar, Anuj; Srinivas, Darbha (Catalysis Today, 2012)
Framework Ti-substituted, three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, were prepared by direct hydrothermal synthesis method. These catalysts showed catalytic activity higher than the hitherto known titanosilicates for the oxidation of cyclic olefins (cyclohexene and cyclooctene) with tert.-butyl hydroperoxide. An epoxide selectivity of 100% and olefin conversion greater than 92% were obtained. Cubic Ti-SBA-16 with interconnected cage-like mesopore structure was more active than hexagonal Ti-SBA-12. X-ray diffraction and diffuse reflectance UV-vis, Fourier transform infrared, Raman and electron paramagnetic resonance spectroscopies provided evidence for the substitution of Ti4+ (for Si4+) in the framework locations. The catalytic activity correlated with the concentration of framework-substituted, tetrahedral Ti4+ ions. Easy accessibility of the active sites and the three-dimensional mesoporous structure are the possible causes for the superior activity of these titanosilicate catalysts. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Epoxidation of cyclic olefins; mesoporous materials; Molecular sieves; Selective oxidation; Ti-SBA-12; Ti-SBA-16; Titanosilicates

Direct synthesis of amides from amines using mesoporous Mn-SBA-12 and Mn-SBA-16 catalysts - Kumar, Anuj; Nepak, Devadutta; Srinivas, Darbha (Catalysis Communications, 2013)
Manganese incorporated SBA-12 and SBA-16 catalyze the tandem reaction of aliphatic primary amine, aerial oxygen and ammonia solution at moderate conditions producing amide in yields as high as 50 mol%. The Mn-SBA-12 and Mn-SBA-16 catalysts with Si/Mn output molar ratio in the range 230 to 748 were prepared by the direct hydrothermal synthesis method and characterized. Weak acidity and Mn in +3 oxidation state are the key factors enable the synthesis of product amide in high yields. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aerial oxidation; Amide synthesis; Benzyl amine; Manganese incorporated SBA-12 and SBA-16; Mesoporous Mn-silica catalyst

Hydroxylation of phenol with hydrogen peroxide catalyzed by Ti-SBA-12 and Ti-SBA-16 - Kumar, Anuj; Srinivas, Darbha (Journal of Molecular Catalysis A-Chemical, 2013)
We report here, for the first time, the application of ordered, three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, as reusable solid catalysts, for hydroxylation of phenol, an industrially important organic transformation. The reactions were conducted using 30% aqueous H2O2 as oxidant. The catalysts of this work are more efficient than the hitherto known mesoporous Ti-silicates. They are more para-product selective than TS-1 and other titanosilicates. Ti-SBA-12 exhibited higher activity and hydroquinone/catechol selectivity (by nearly two times) than Ti-SBA-16. H2O2 efficiency of similar to 90 mol% was obtained. Our study reveals that framework substituted Ti with pseudo-tetrahedral geometry, three-dimensional mesoporosity as well as surface structure are the unique features responsible for the high catalytic activity and selectivity of these titanosilicate catalysts. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Catalytic liquid-phase hydroxylation of phenol; Molecular sieves; Ordered mesoporous titanosilicates; Oxidation with hydrogen peroxide; Ti-SBA-12; Ti-SBA-16

Three-dimensional, mesoporous titanosilicates as catalysts for producing biodiesel and biolubricants - Kotwal, Mehejabeen; Kumar, Anuj; Darbha, Srinivas (Journal of Molecular Catalysis A-Chemical, 2013)
The application of three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, as reusable solid acid catalysts for producing biodiesel and biolubricants is reported for the first time. Biodiesel was prepared by esterification of oleic acid with monohydric methanol and biolubricants by esterification with polyhydric alcohols (glycerol, trimethylolpropane, neopentyl glycol and pentaerythritol). High catalytic activity of these catalysts is attributed to the presence of dispersed Lewis acidic Ti sites and mesoporosity in the structure. Biodiesel yields as high as 90 mol% were obtained at 443 K. Surface hydrophobicity of the catalyst has also a predominant role, especially, in reactions involving polyhydric alcohols. In those reactions, Ti-SBA-16 showed higher catalytic activity than Ti-SBA-12. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; Esterification of fatty acid; Lubricant basestocks; mesoporous materials; Ti-SBA-12; Ti-SBA-16; Titanosilicates

Novel pyrazole derivatives as inhibitors of Leishmania donovani: an integrated approach combining in vitro analysis and mechanistic insights - Kumari, Diksha; Kour, Jaspreet; Kumar, Anuj; Sangral, Monica; Singh, Shashank K.; Sawant, Sanghapal D.; Singh, Kuljit (Bioorganic Chemistry, 2025)
Leishmaniasis is a neglected tropical disease that continues to be a global public health problem, leading to a disastrous impact on poor rural people. The present therapeutic arsenal faces the limitations of drug resistance and toxicity concerns, raising a great need to identify novel chemical scaffolds that are potent, non-toxic, and cost-effective. Heterocycles comprise a distinctive class of molecules exhibiting a wide array of physical, chemical, and biological characteristics and occupy a prominent position in pharmaceutical applications. In the present study, we aimed to investigate three series of pyrazole derivatives synthesized previously by our group for their anti-leishmanial potential against Leishmania donovani parasites. Primarily, 29 compounds were evaluated using an Alamar blue dye-based assay for their inhibitory potency, out of which six molecules (4a, 4b, 4c, 4j, 7a, and 7d) were active with >50 % growth inhibition at a 50 mu M dose. Among them, three molecules (4b, 4j, and 7d) showed remarkable leishmanicidal potency with 50 % inhibitory concentration (IC50) in the range of 5 to 13 mu M. Toxicity analysis revealed that the potential hit (4j) represented a promising cytocompatibility profile along with noteworthy activity against L. donovani intracellular amastigotes. Furthermore, the in-depth mechanistic evaluation using scanning electron microscopy, reactive oxygen species (ROS) generation, mitochondrial membrane potential (Delta Psi m) determination, ATP quantification, cell cycle analysis, and lipid accumulation assay confirms the inhibitory potential of compound 4j. Thus, the present study represents pyrazole derivatives as a potential scaffold for the development of novel chemotherapeutics against leishmaniasis.
Keywords: Cell death; drug discovery; FACS analysis; leishmaniasis; Pyrazole derivatives; Reactive Oxygen Species (ROS); scanning electron microscopy